Conductive polymer solution for capacitors, solid electrolytic capacitor and manufacturing method
Patent Information
- Application Number
- JP2023138286
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-28
- Publication Date
- 2025-03-12
AI Technical Summary
【0023】 固体電解コンデンサの静電容量を向上させることができる。
Smart Images

Figure 2025032804000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a conductive polymer solution for a capacitor for forming a solid electrolyte layer in a solid electrolytic capacitor, a solid electrolytic capacitor in which a solid electrolyte layer is interposed between an anode foil and a cathode foil, and a method for manufacturing a solid electrolytic capacitor using the conductive polymer solution for a capacitor. [Background technology]
[0002] An electrolytic capacitor has anode and cathode foils made of valve metals such as tantalum or aluminum. The anode foil is enlarged by forming the valve metal into a sintered or etched foil, and the enlarged surface has a dielectric oxide film formed by anodizing or other treatment. An electrolyte is interposed between the anode and cathode foils.
[0003] Electrolytic capacitors have the advantage that they can easily obtain a large capacitance compared to other types of capacitors because the specific surface area can be increased by expanding the surface area of the anode foil. Electrolytic capacitors contain electrolyte in the form of an electrolytic solution. The contact area of the electrolyte with the dielectric oxide film of the anode foil increases. This makes it easier to further increase the capacitance of electrolytic capacitors.
[0004] In recent years, solid electrolytic capacitors, which use a solid electrolyte with higher conductivity than the electrolyte, have also been attracting attention. Solid electrolytic capacitors use a solid electrolyte with higher conductivity than the electrolyte, and can achieve low equivalent series resistance (ESR). Manganese dioxide and 7,7,8,8-tetracyanoquinodimethane (TCNQ) complexes are known as solid electrolytes.
[0005] In addition, conductive polymers derived from monomers with π-conjugated double bonds, such as poly(3,4-ethylenedioxythiophene) (PEDOT), which has excellent adhesion to dielectric oxide films, are rapidly becoming popular as solid electrolytes. Conductive polymers use polystyrene sulfonate (PSS) as a dopant to achieve high conductivity. Therefore, solid electrolytic capacitors have the advantage of low equivalent series resistance (ESR).
[0006] A solid electrolyte containing a conductive polymer is formed by applying or impregnating a conductive polymer dispersion between an anode foil and a cathode foil, and drying the dispersion medium. The conductive polymer dispersion is a dispersion of a conductive polymer, and for example, water is used as the dispersion medium to disperse the conductive polymer in water. The conductive polymer is produced by mixing a monomer, which becomes a monomer unit of the conductive polymer, a dopant, and an oxidizing agent, and subjecting the mixture to chemical oxidative polymerization.
[0007] The conductive polymer dispersion containing PEDOT doped with PSS is adjusted to pH 3 to 13 with an alkaline compound (see, for example, Patent Document 1). If the pH is less than 3, the acidity is too strong and corrosion of the dielectric oxide film and the cathode foil cannot be prevented, whereas if the pH exceeds 13, the conductive polymer is de-doped, resulting in insufficient conductivity of the solid electrolyte layer.
[0008] However, it continues to be pointed out that even if the pH of the conductive polymer dispersion is adjusted to 3 to 13, the ESR and capacitance are not sufficient in terms of performance (see, for example, Patent Document 2). Therefore, a proposal has been presented to adjust the content of the alkaline compound based on the neutralization equivalent of the conductive polymer. However, if the pH of the conductive polymer dispersion is shifted to the alkaline side, dedoping of PSS is likely to occur, so it is still considered preferable to have a range from weak acidity to neutrality with an upper limit of pH 8 at most (see, for example, Patent Document 3).
[0009] The purpose of the alkaline compound is to adjust the pH, so theoretically any alkaline compound is conceivable for this purpose only. However, in practice, ammonia is often used as the alkaline compound added to the conductive polymer dispersion. Ammonia is weakly basic and it is difficult to undo PSS from PEDOT, but if the basicity is stronger than ammonia, the undoping of PSS increases, and the ESR increases even at a pH of 8 or less (see, for example, Patent Document 3).
[0010] In addition, ammonia is volatile and can be easily removed by a process involving heating, making it difficult to de-dop PSS. Furthermore, ammonia has a small molecular size, and even if it forms an ion pair with PSS, it can suppress the reduction in effective conjugation length caused by the twisting of the PEDOT main chain, making it difficult to de-dop PSS.
[0011] In summary, in order to adjust the pH of the conductive polymer dispersion, ammonia, which is weakly basic, should be used, and the pH should be controlled to be equal to or lower than 8. However, although the range of pH 8 may possibly be suggested as meaning a range from weakly acidic to neutral, in reality, it would be more realistic to optimize the pH in the range of 5 or lower (see, for example, Patent Document 3).
[0012] Regarding the suppression of ESR, the use of an inorganic alkali compound alone or an organic alkali compound alone tends to improve the withstand voltage characteristics, but it has been shown that the increase in ESR in a high-temperature environment is not sufficiently suppressed, and a liquid composition containing two or more types of alkali compounds has also been proposed (see, for example, Patent Document 3). The liquid composition is a conductive polymer dispersion. The two or more types of alkali compounds are essentially a combination of ammonia and amine. [Prior art documents] [Patent documents]
[0013] [Patent Document 1] JP 2006-287182 A [Patent Document 2] JP 2014-67949 A [Patent Document 3] International Publication No. 2018 / 123255 Summary of the Invention [Problem to be solved by the invention]
[0014] Thus, there has been technological progress in terms of suppressing the ESR of solid electrolytic capacitors. However, since it was pointed out that conductive polymer dispersions with a pH of 3 to 13 are not sufficient in terms of capacitance performance, it cannot be said that sufficient research has been conducted on measures to fully utilize the capacitance of solid electrolytic capacitors from the perspective of the composition of conductive polymer dispersions. Moreover, in recent years, electronic and electrical devices have become significantly smaller and more powerful. Therefore, there is a demand for further improvement in capacitance of solid electrolytic capacitors as well.
[0015] The present invention has been proposed to solve the above-mentioned problems, and an object of the present invention is to provide a conductive polymer solution for a capacitor for increasing the capacitance of a solid electrolytic capacitor, a solid electrolytic capacitor with increased capacitance, and a manufacturing method thereof. [Means for solving the problem]
[0016] In order to solve the above problems, the conductive polymer solution for a capacitor of the present embodiment contains a polymer of 3,4-ethylenedioxythiophene in which a methylenephosphonic acid group is introduced into an ethylenedioxy skeleton, and an amine other than ammonia.
[0017] The amine may be a secondary amine or a tertiary amine.
[0018] The pH may be 10 or less.
[0019] The pH may be 9 or greater.
[0020] The pH may be around 9.
[0021] In order to solve the above problems, the solid electrolytic capacitor of the present embodiment includes an anode foil having a dielectric oxide film formed thereon, and a solid electrolyte layer including a conductive polymer, the conductive polymer being a polymer of 3,4-ethylenedioxythiophene having a methylenephosphonic acid group introduced into an ethylenedioxy skeleton, and the solid electrolyte layer containing an amine other than ammonia.
[0022] In order to solve the above problems, the method for manufacturing a solid electrolytic capacitor of the present embodiment is a method for manufacturing a solid electrolytic capacitor having an anode foil on which a dielectric oxide film is formed, and includes a solid electrolyte layer formation step of adhering such a conductive polymer solution for a capacitor to the anode foil and drying it. Effect of the Invention
[0023] The capacitance of the solid electrolytic capacitor can be improved. [Brief description of the drawings]
[0024] [Figure 1] 1 is a scatter plot showing the capacitances measured at a measurement frequency of 120 Hz for Examples 1 to 5 and Comparative Example 1. [Diagram 2] 1 is a scatter plot showing the capacitances measured at a measurement frequency of 10 kHz for Examples 1 to 5 and Comparative Example 1. [Diagram 3] FIG. 2 is a scatter plot showing ESR measured at a measurement frequency of 100 kHz for Examples 1 to 5 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0025] Hereinafter, a conductive polymer solution for a capacitor, a solid electrolytic capacitor, and a manufacturing method thereof according to embodiments of the present invention will be described. Note that the present invention is not limited to the embodiments described below.
[0026] (Conductive polymer solution for capacitors) A conductive polymer solution for capacitors (hereinafter referred to as polymer solution) is a solution for forming a solid electrolyte layer in a solid electrolytic capacitor. A solid electrolytic capacitor is a passive element that stores and discharges electric charge by electrostatic capacitance, and an anode foil and a cathode foil on which a dielectric oxide film is formed are opposed to each other via a separator, and a solid electrolyte layer is interposed between the anode foil and the cathode foil. The solid electrolyte layer contains a conductive polymer. The conductive polymer of the solid electrolyte layer is dissolved in the polymer solution. The solid electrolyte layer is formed by applying the polymer solution to the dielectric oxide film of the anode foil and drying it.
[0027] The conductive polymer is a polymer of 3,4-ethylenedioxythiophene in which a methylenephosphonic acid group has been introduced into the ethylenedioxy skeleton. As an example of this conductive polymer, as represented by the following chemical formula (A), a polymer of 3,4-ethylenedioxythiophene in which a methylenephosphonic acid group has been introduced into the 2-position of the ethylenedioxy skeleton can be given. Alternatively, as an example of this conductive polymer, a polymer of 3,4-ethylenedioxythiophene in which a methylenephosphonic acid group has been introduced into the 1-position of the ethylenedioxy skeleton can be given.
[0028] [ka]
[0029] The conductive polymer may be a homopolymer formed by polymerizing only the monomer of 3,4-ethylenedioxythiophene having a methylenephosphonic acid group introduced into the ethylenedioxy skeleton, or a copolymer containing this monomer unit and 3,4-ethylenedioxythiophene or a derivative of 3,4-ethylenedioxythiophene. Hereinafter, the polymer of 3,4-ethylenedioxythiophene having a methylenephosphonic acid group introduced into the ethylenedioxy skeleton is referred to as phosphonic acid group-introduced PEDOT.
[0030] In phosphonic acid group-introduced PEDOT, the methylene phosphonic acid group in the side chain acts as a hydrogen ion-donating dopant. Therefore, phosphonic acid group-introduced PEDOT exhibits conductivity as a self-doped conductive polymer. Furthermore, as the dissociation of the methylene phosphonic acid group progresses, the solubility in solvents improves, and phosphonic acid group-introduced PEDOT becomes soluble in water.
[0031] An amine is added to the polymer solution in which the phosphonic acid group-introduced PEDOT is dissolved. The pH of the polymer solution is adjusted to more than 8, from about 9 to 10 or less, by adding the amine. As the amine, alkylamines and alkanolamines are preferable, and secondary amines or tertiary amines are particularly preferable because of their strong basicity. The amine may be a derivative having a substituent. Around pH 9 is near pH 9, which is pH 8.5 to 9.5.
[0032] Examples of secondary amines include dimethylamine, diethylamine, dipropylamine, methylethylamine, diethanolamine, etc. Examples of tertiary amines include trimethylamine, triethylamine, ethyldimethylamine, dimethyloctylamine, diethyloctylamine, dimethylaminoethanol, dimethylaminoethoxyethanol, etc.
[0033] In such a polymer solution, the phosphonic acid group-introduced PEDOT is a self-doped conductive polymer, and is therefore more difficult to undo than a conductive polymer made of poly(3,4-ethylenedioxythiophene) (PEDOT) doped with polystyrene sulfonic acid (PSS) (hereinafter referred to as PEDOT:PSS). Therefore, the pH of the polymer solution can be increased to the alkaline side. When the polymer solution with an alkaline pH is dried, the phosphonic acid group-introduced PEDOT solubilized in the solution precipitates.
[0034] Here, the solid electrolyte layer creates a conductive path between the dielectric oxide film and the cathode foil, and the solid electrolyte layer becomes the true cathode. If the phosphonic acid group-introduced PEDOT cannot be sufficiently filled in the surface expansion layer of the anode foil, the opposing area of the anode and cathode will be small. If the opposing area is small, the capacitance of the solid electrolytic capacitor will decrease. Moreover, in recent years, the surface expansion layer of the anode foil has become denser and the voids have become smaller in order to expand the surface area in order to improve capacitance.
[0035] However, since the phosphonic acid group-introduced PEDOT is solubilized in the solution by the amine, it is fully filled into the surface-expanding layer of the anode foil, improving the capacitance of the solid electrolytic capacitor. Moreover, the methylene phosphonic acid group of the phosphonic acid group-introduced PEDOT has high adsorption to the dielectric oxide film, improving the adhesion between the solid electrolyte layer and the dielectric oxide film, and reducing the dissociation area between the dielectric oxide film and the solid electrolyte layer.
[0036] However, if the pH is too high, even phosphonic acid group-introduced PEDOT will undergo dedoping, and the ESR of the solid electrolytic capacitor will rise. The ammonia used to adjust the pH of PEDOT:PSS is weakly basic and has a small molecular size, so when the polymer solution is weakly alkaline at around pH 9, the aggregation suppression effect of phosphonic acid group-introduced PEDOT is still low, and the phosphonic acid group-introduced PEDOT cannot be stably made into small particles and solubilized, not only causing the polymer solution itself to gel, but also causing the ESR of the solid electrolytic capacitor to become extremely high.
[0037] In this regard, amines, being strongly basic and having a bulky molecular structure, promote the dissociation of phosphonic acid groups, thereby suppressing the aggregation of phosphonic acid group-introduced PEDOT and reducing the particle size and solubility of phosphonic acid group-introduced PEDOT even when the polymer solution is in the relatively weakly alkaline range of pH 9 to 10. That is, when hydrogen atoms of the phosphonic acid groups of phosphonic acid group-introduced PEDOT are hydrogen-bonded with each other, aggregation of phosphonic acid group-introduced PEDOT is caused, but when these hydrogen atoms are replaced by amines, hydrogen bonding does not occur and aggregation of phosphonic acid group-introduced PEDOT is suppressed.
[0038] Therefore, when the phosphonated PEDOT and the amine are added to the polymer solution, the phosphonated PEDOT can be made small and solubilized without agglomeration or dedoping of the phosphonated PEDOT in the polymer solution, and the capacitance of the solid electrolytic capacitor having a solid electrolyte layer containing the solubilized phosphonated PEDOT is improved.
[0039] When ammonia is used instead of amine, the aggregation of phosphonic acid group-introduced PEDOT is finally suppressed when the pH of the polymer solution is increased to 10 or more. Then, the particles of phosphonic acid group-introduced PEDOT become finer and begin to dissolve, but the improvement in the capacitance of the solid electrolytic capacitor is still slight. On the other hand, when the pH exceeds 10, dedoping increases and the ESR begins to increase. Therefore, ammonia is excluded from the group of alkaline compounds that can be added to the polymer solution. In other words, the polymer solution does not contain ammonia.
[0040] However, even when amine is added, the ESR starts to rise when the pH exceeds 10. Amine has a bulky molecular structure. When many amines are close to the phosphonic acid group-introduced PEDOT, the dedoping proceeds slowly, and the ESR starts to rise. The reason why the dedoping proceeds slowly is due to the shortening of the effective conjugation length caused by the twisting of the main chain of the phosphonic acid group-introduced PEDOT. Therefore, it is preferable to set the pH of the polymer solution to 10 or less. In addition, the combination of PEDOT:PSS and amine is not preferable because the amine has a strong basicity and a bulky molecular structure, and therefore dedoping proceeds immediately when the pH exceeds the neutralization point of PSS.
[0041] The solvent of the polymer solution is not particularly limited as long as it dissolves the phosphonic acid group-introduced PEDOT. The solvent of the polymer solution is typically water, but may also be an organic solvent or a mixture of an organic solvent and water. Examples of the organic solvent include polar solvents, alcohols, esters, hydrocarbons, carbonate compounds, ether compounds, chain ethers, heterocyclic compounds, and nitrile compounds.
[0042] Examples of polar solvents include N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide. Examples of alcohols include methanol, ethanol, propanol, and butanol. Examples of esters include ethyl acetate, propyl acetate, and butyl acetate. Examples of hydrocarbons include hexane, heptane, benzene, toluene, and xylene. Examples of carbonate compounds include ethylene carbonate and propylene carbonate. Examples of ether compounds include dioxane and diethyl ether. Examples of chain ethers include ethylene glycol dialkyl ether, propylene glycol dialkyl ether, polyethylene glycol dialkyl ether, and polypropylene glycol dialkyl ether. Examples of heterocyclic compounds include 3-methyl-2-oxazolidinone. Examples of nitrile compounds include acetonitrile, glutarodinitrile, methoxyacetonitrile, propionitrile, and benzonitrile.
[0043] The polymer solution may further contain additives such as polyhydric alcohols. Examples of polyhydric alcohols include polyethylene glycol, 1-hexanol, ethylene glycol, diethylene glycol, triethylene glycol, glycerin, or a combination of two or more of these. Since polyhydric alcohols have a high boiling point, they remain in the solid electrolyte layer even after the polymer solution is dried. Furthermore, the polymer solution may contain conventional additives such as organic binders, surfactants, dispersants, antifoaming agents, coupling agents, antioxidants, and ultraviolet absorbers.
[0044] The method for producing such a polymer solution is not particularly limited, but it can be obtained, for example, by the following production method.
[0045] First, the method for producing phosphonic acid group-introduced PEDOT is as follows. That is, 3,4-ethylenedioxythiophene in which a methylene group having a halogen substituent has been introduced into the ethylenedioxy skeleton is heated in the presence of an acid catalyst such as sulfuric acid, paratoluenesulfonic acid, or methanesulfonic acid. The Michaelis-Arbuzov transfer reaction is caused between 3,4-ethylenedioxythiophene in which a methylene group having a halogen substituent has been introduced and tris(trialkylsilyl)phosphite, and the halogen is replaced with a phosphonic acid bis(trialkylsilyl) group or a phosphonic acid diester group. Then, a basic solution such as a solution of sodium carbonate, potassium carbonate, or ammonia is applied to the compound after the reaction to cause deprotection.
[0046] Next, 3,4-ethylenedioxythiophene with methylenephosphonic acid groups introduced into the ethylenedioxy skeleton is mixed with a supporting electrolyte or an oxidizing agent to produce phosphonic acid group-introduced PEDOT by electrolytic polymerization or chemical polymerization. The phosphonic acid group-introduced PEDOT may be dissolved in a solvent after removing residual monomers and impurities by purification means such as ultrafiltration, cation exchange, and anion exchange. The amine may be added after the phosphonic acid group-introduced PEDOT is dissolved in a solvent, and dissolution treatment may be performed using, for example, an ultrasonic homogenizer.
[0047] (Solid electrolytic capacitor) The cathode foil and anode foil of a solid electrolytic capacitor are foil bodies made of valve metal and stretched. Valve metals include aluminum, tantalum, niobium, niobium oxide, titanium, hafnium, zirconium, zinc, tungsten, bismuth, and antimony. A surface-expanding layer is formed on one or both sides of the anode body. The surface-expanding layer is a sintered body made by sintering valve metal powder, or an etched layer made by etching a stretched foil, and is composed of voids between densely packed powder particles, or tunnel-like or spongy pits. The cathode foil may have a surface-expanding layer formed thereon like the anode body, or may be a plain foil without a surface-expanding layer.
[0048] The dielectric oxide film is formed on one or both sides of the anode foil on which the surface-expanding layer is formed. The dielectric oxide film is typically an oxide film formed on the surface layer of the anode body, and if the anode foil is made of aluminum, it is an aluminum oxide layer formed by oxidizing the surface of the surface-expanding layer. In the chemical conversion treatment for forming the dielectric oxide film, a voltage is applied to the anode body in a chemical conversion solution so as to achieve a desired withstand voltage. The chemical conversion solution is a solution that does not contain halogen ions, and is, for example, a phosphoric acid-based chemical conversion solution such as ammonium dihydrogen phosphate, a boric acid-based chemical conversion solution such as ammonium borate, or an adipic acid-based chemical conversion solution such as ammonium adipate.
[0049] The cathode foil may have a natural oxide film or a thin oxide film (about 1 to 10 V) formed by chemical conversion treatment. The natural oxide film is formed by the reaction of the cathode foil with oxygen in the air. Furthermore, the cathode foil may have a layer made of a metal nitride, a metal carbide, or a metal carbonitride formed by a vapor deposition method, or a layer containing carbon formed on the surface.
[0050] The cathode foil may be a laminate of a metal layer and a carbon layer. The cathode foil is disposed with the carbon layer facing the anode foil. The carbon layer is formed by coating a slurry or paste on the solid electrolyte layer after the solid electrolyte layer is formed on the anode body, and then curing the layer by heating. The metal layer is, for example, a silver layer, and is formed by coating a slurry or paste on the carbon layer, and then curing the layer by heating.
[0051] The solid electrolyte layer is formed by using a polymer solution. The polymer solution is immersed in the polymer solution and then dried to attach the solid electrolyte layer to various objects. The objects are anode foils, or anode foils, cathode bodies, and separators, or capacitor elements that are assemblies incorporating anode foils, cathode foils, and separators.
[0052] The capacitor element may include a second solid electrolyte layer forming step for forming a solid electrolyte layer in addition to the solid electrolyte layer formed using the polymer solution containing the phosphonic acid group-introduced PEDOT. The second solid electrolyte layer may be formed, for example, by chemical polymerization or electrolytic polymerization in which a monomer of 3,4-ethylenedioxythiophene or a derivative thereof is polymerized, or by using a dispersion liquid in which a polymer of 3,4-ethylenedioxythiophene or a derivative thereof is dispersed.
[0053] After the immersion, the solvent of the polymer solution is removed by a drying process. The temperature environment in the drying process is, for example, 40°C to 200°C, and the drying time is, for example, in the range of 3 minutes to 180 minutes. The drying process may be repeated multiple times. Drying may be performed in a reduced pressure environment, for example, by reducing the pressure to 5 kPa to 100 kPa. In addition to immersion, the polymer solution may be applied by dripping or spraying.
[0054] Examples of the separator include cellulose papers such as kraft, Manila hemp, esparto, hemp, and rayon, and mixed papers thereof; polyester-based resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and derivatives thereof; polytetrafluoroethylene-based resins, polyvinylidene fluoride-based resins, vinylon-based resins, polyamide-based resins such as aliphatic polyamides, semi-aromatic polyamides, and fully aromatic polyamides; polyimide-based resins, polyethylene resins, polypropylene resins, trimethylpentene resins, polyphenylene sulfide resins, acrylic resins, and polyvinyl alcohol resins. These resins can be used alone or in combination.
[0055] The separator separates the anode body and the cathode body to prevent shorting between them, and also holds the solid electrolyte between the anode body and the cathode body. If the shape of the solid electrolyte can be maintained by itself and the cathode body and the anode body can be isolated by the solid electrolyte, the separator can be eliminated from the solid electrolytic capacitor.
[0056] The capacitor element may be a laminated type in which the anode foil and the cathode foil are alternately laminated with a separator sandwiched therebetween, or a wound type in which the anode foil and the cathode foil are alternately laminated with a separator sandwiched therebetween and wound. Alternatively, the capacitor element may be a flat type in which a solid electrolyte layer is formed on an individual anode foil, and then a carbon layer and a silver layer are formed on the solid electrolyte layer, or a flat type in which a carbon paste or a silver paste is applied and at the same time a copper foil is bonded as a lead terminal. In the case of the flat type, there is no cathode foil or separator, and the carbon layer and the silver layer correspond to the cathode foil of the solid electrolytic capacitor.
[0057] The solid electrolytic capacitor may include only a solid electrolyte layer, or may also include an electrolyte solution. The electrolyte solution is impregnated into the capacitor element after the solid electrolyte layer is formed. The electrolyte solution is responsible for repairing at least the dielectric oxide film.
[0058] The solvent of the electrolyte is not particularly limited, but a protonic organic polar solvent or an aprotic organic polar solvent can be used. As the protonic polar solvent, monohydric alcohols, polyhydric alcohols, oxyalcohol compounds, water, etc. are typified, such as ethylene glycol or propylene glycol. As the aprotic polar solvent, sulfones, amides, lactones, cyclic amides, nitriles, sulfoxides, etc. are typified, such as sulfolane, γ-butyrolactone, ethylene carbonate, or propylene carbonate.
[0059] The solute contained in the electrolytic solution includes anion and cation components, and is typically an organic acid such as adipic acid or benzoic acid or its salt, an inorganic acid such as boric acid or phosphoric acid or its salt, or a complex compound of an organic acid such as borodisalicylic acid and an inorganic acid or its ion-dissociable salt, and is used alone or in combination of two or more. Examples of the salts of these organic acids, salts of inorganic acids, and at least one salt of a complex compound of an organic acid and an inorganic acid include ammonium salts, quaternary ammonium salts, quaternary amidinium salts, amine salts, sodium salts, potassium salts, etc. An acid that becomes an anion and a base that becomes a cation may be added separately to the electrolytic solution as solute components.
[0060] Furthermore, other additives can be added to the electrolyte. Examples of additives include polyethylene glycol, complex compounds of boric acid and polysaccharides (mannitol, sorbitol, etc.), complex compounds of boric acid and polyhydric alcohols, boric acid esters, nitro compounds, phosphate esters, colloidal silica, etc. These may be used alone or in combination of two or more. The nitro compounds suppress the generation of hydrogen gas in the electrolytic capacitor. Examples of nitro compounds include o-nitrobenzoic acid, m-nitrobenzoic acid, p-nitrobenzoic acid, o-nitrophenol, m-nitrophenol, p-nitrophenol, etc.
[0061] The capacitor element is inserted into a cylindrical exterior case with a bottom. A sealing body is attached to the open end of the exterior case, and the capacitor element is sealed by crimping the open end. The sealing body is made of rubber, or includes a laminate of rubber and a hard substrate. Examples of rubber include ethylene propylene rubber and butyl rubber. An anode lead and a cathode lead are connected to the anode body and the cathode body, and the anode lead and the cathode lead are drawn out from the sealing body.
[0062] In addition to being housed in a bottomed cylindrical exterior case, the capacitor element may be sealed with a laminate film or molded with a resin. Examples of the molding resin include heat-resistant resin and insulating resin. The molding resin may be formed into a thin film by a method such as dip coating or printing. In addition, the exterior may be omitted for a flat-plate type capacitor element. EXAMPLES
[0063] The polymer solution, the solid electrolytic capacitor and the manufacturing method thereof will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.
[0064] Example 1 The polymer solution of Example 1 was prepared as follows, and the solid electrolytic capacitor of Example 1a was prepared using the polymer solution of Example 1. First, phosphonic acid group-introduced PEDOT was added to water, and stirring was performed using ultrasonic waves. After stirring, ethyldimethylamine was added to the polymer solution until the pH of the polymer solution reached 9. This produced the polymer solution of Example 1, in which the concentration of phosphonic acid group-introduced PEDOT was 2 wt %.
[0065] Next, for the solid electrolytic capacitor of Example 1a, aluminum foil was prepared as an anode foil and a cathode foil. A surface expansion layer was formed on the surface of the aluminum foil for the anode, and a dielectric oxide film was formed by further performing a chemical conversion treatment. A lead wire, which is an electrode extraction means, was connected to the anode foil and the cathode foil, and the anode foil and the cathode foil were wound with a manila separator interposed therebetween to prepare a capacitor element. In forming the surface expansion layer, an alternating current was passed through the aluminum foil in a solution containing hydrochloric acid to form a spongy etching pit. The dielectric oxide film was formed by performing a chemical conversion treatment in an ammonium adipate solution on the aluminum foil on which the surface expansion layer was formed, and setting the chemical conversion voltage to 55V.
[0066] This capacitor element was subjected to a chemical repair process. In the chemical repair process, the anode foil of the capacitor element was immersed in an ammonium dihydrogen phosphate solution at 90°C for 24 minutes. While immersed in the solution, a current of 10 mA was passed through the capacitor element with an applied voltage of 58 V. After the capacitor element was removed from the ammonium dihydrogen phosphate solution, it was washed with pure water and then left to dry in a 105°C temperature environment for 30 minutes.
[0067] After drying the capacitor element, the capacitor element was immersed in the polymer solution of Example 1 while reducing the pressure inside the capacitor element. The capacitor element was then left to stand for 30 minutes in a temperature environment of 100°C to dry it. As a result, a solid electrolyte containing phosphonic acid group-introduced PEDOT was formed in the capacitor element.
[0068] The capacitor element on which the solid electrolyte was formed was 6.3 mm in diameter and 5.8 mm in height, and was inserted into a cylindrical aluminum exterior case with a bottom. A rubber seal was attached to the open end of the aluminum exterior case, and the aluminum exterior case was sealed by crimping. Then, an aging treatment was performed to produce the solid electrolytic capacitor of Example 1a.
[0069] Comparative Example 1 A polymer solution of Comparative Example 1 and a solid electrolytic capacitor of Comparative Example 1a were produced corresponding to the polymer solution of Example 1 and the solid electrolytic capacitor of Example 1a. Ammonia was added to the polymer solution of Comparative Example 1 instead of the amine added to the polymer solution of Example 1. Except for the point that the amine was changed to ammonia, the polymer solution was the same as that of Example 1, including the point that phosphonic acid group-introduced PEDOT was dissolved, the point that water was used as a solvent, and the point that ammonia was added until the pH of the polymer solution reached 9.
[0070] The solid electrolytic capacitor of Comparative Example 1a was produced using the polymer solution of Comparative Example 1. Except for the fact that the solid electrolyte layer was formed from the polymer solution of Comparative Example 1, the solid electrolytic capacitor of Comparative Example 1a had the same configuration as the solid electrolytic capacitor of Example 1a and was produced by the same manufacturing method and under the same conditions.
[0071] (Characteristics test) The filter permeability of the polymer solutions of Example 1 and Comparative Example 1 was measured. In the filter permeability measurement test, 2.5 ml of the sample polymer solution was collected in a syringe (SS-02LZ manufactured by Terumo) and connected to a membrane filter (PVDF membrane) with a pore size of 0.1 μm, and the syringe was pressurized to achieve a flow rate of 0.1 ml per second to send the polymer solution to the membrane filter. The measurement results were judged as OK when 90% or more of the polymer solution collected in the syringe passed through the membrane filter, and NG when the amount of the polymer solution passing through the membrane filter was less than 90%.
[0072] In addition, the capacitance (Cap) and equivalent series resistance (ESR) of the solid electrolytic capacitors of Example 1a and Comparative Example 1a were measured. Cap and ESR were measured at a temperature of 20°C using an LCR meter (model number ZM2376, manufactured by NF Corporation). Cap was measured at two frequencies, 120 Hz and 10 kHz, and ESR was measured at a frequency of 100 kHz. The DC bias was 1.5 V, and the AC current level was a sine wave of 1.0 Vrms.
[0073] The measurement results are shown in Table 1 below. (Table 1) TIFF2025032804000003.tif51161
[0074] As shown in Table 1, the polymer solution of Comparative Example 1 gelled in a short time after preparation at pH 9, and the phosphonic acid group-introduced PEDOT was not solubilized. Therefore, the ESR of the solid electrolytic capacitor of Comparative Example 1a was very high, and the capacitance was low. The polymer solution of Comparative Example 1 contained phosphonic acid group-introduced PEDOT and ammonia.
[0075] On the other hand, the polymer solution of Example 1 was confirmed to have liquid permeability in a filter with a pore size of 0.1 μm at a pH of 9. That is, the polymer solution of Example 1 was not gelled, and the phosphonic acid group-introduced PEDOT contained in the polymer solution of Example 1 was solubilized. Therefore, the solid electrolytic capacitor of Example 1a has a higher capacitance than that of Comparative Example 1. Furthermore, dedoping did not occur at a pH of 9, and the ESR of the solid electrolytic capacitor of Example 1a is low.
[0076] Thus, it was confirmed that a polymer solution of pH 9 containing phosphonic acid group-introduced PEDOT and amine improves the capacitance of solid electrolytic capacitors and keeps the ESR low.
[0077] (Examples 2 to 5) Polymer solutions of Examples 2 to 5 and solid electrolytic capacitors of Examples 2a to 5a were produced. The polymer solutions of Examples 2 to 5 are the same as Example 1 in that they contain amine, but the type of amine is different. The polymer solution of Example 2 contains dimethylamine. The polymer solution of Example 3 contains diethylamine. The polymer solution of Example 4 contains trimethylamine. The polymer solution of Example 5 contains propylamine.
[0078] The polymer solutions of Examples 2 to 5 were the same as the polymer solution of Example 1, except that the type of amine was changed, including the fact that phosphonic acid group-introduced PEDOT was dissolved therein, that water was used as the solvent, and that amine was added until the pH of the polymer solution reached 9. The solid electrolytic capacitors of Examples 2a to 5a had the same configuration as the solid electrolytic capacitor of Example 1a, except that the solid electrolyte layer was formed from the polymer solution of Examples 2 to 5, and were produced by the same method and under the same conditions.
[0079] (Characteristics test) The filter liquid permeability of the polymer solutions of Examples 2 to 5 was measured. The electrostatic capacitance (Cap) and equivalent series resistance (ESR) of the solid electrolytic capacitors of Examples 2a to 5a were also measured. The methods and conditions of the filter liquid permeability test and the Cap and ESR measurement tests were the same as those of Example 1 and Comparative Example 1, and Example 1a and Comparative Example 1a.
[0080] The measurement results are shown in Table 2 below, together with the results of Comparative Example 1 and Comparative Example 1a. (Table 2) TIFF2025032804000004.tif96161
[0081] As shown in Table 2, the polymer solutions of Examples 2 to 4 showed good results in the test of the liquid permeability through a filter with a pore size of 0.1 μm at a pH of 9. Therefore, the capacitance of the solid electrolytic capacitors of Examples 2a to 4a was high and the ESR was kept low at a pH of 9. Thus, it was confirmed that the polymer solution of pH 9 containing phosphonic acid group-introduced PEDOT and an amine improves the capacitance of the solid electrolytic capacitor and keeps the ESR low, regardless of whether the amine is a secondary amine or a tertiary amine.
[0082] The polymer solution of Example 5 contains a primary amine, but the result of the liquid permeability test of the filter with a pore size of 0.1 μm in Example 5 was that the liquid permeability was less than 90%. However, the phosphonic acid group-introduced PEDOT contained in the polymer solution of Example 5 was not solubilized compared to Comparative Example 1, but was made into small particles. Therefore, the capacitance and ESR of the solid electrolytic capacitor of Example 5a were better than those of Comparative Example 1a.
[0083] Here, the results of Examples 1 to 5 and Comparative Example 1 shown in Tables 1 and 2 are summarized in Figures 1 to 3. Figure 1 is a scatter plot showing the capacitance measured at a measurement frequency of 120 Hz, Figure 2 is a scatter plot showing the capacitance measured at a measurement frequency of 10 kHz, and Figure 3 is a scatter plot showing the ESR measured at a measurement frequency of 100 kHz.
[0084] As shown in Figures 1 to 3, the polymer solutions of Examples 1 to 4 contain secondary amines or tertiary amines, and therefore have strong basicity and bulky molecular structures, which further improves the capacitance and ESR of the solid electrolytic capacitors of Examples 1a to 4a.
[0085] (Examples 6 to 10) Polymer solutions of Examples 6 to 10 and solid electrolytic capacitors of Examples 6a to 11a were produced. The polymer solutions of Examples 6 to 10 differ from Examples 1 to 5 in that the pH is adjusted to 10 with amine. Example 6 corresponds to Example 2, and dimethylamine is added. Example 7 corresponds to Example 3, and diethylamine is added. Example 8 corresponds to Example 4, and trimethylamine is added. Example 9 corresponds to Example 1, and ethyldimethylamine is added. Example 10 corresponds to Example 5, and propylamine is added.
[0086] Other than that, the polymer solutions of Examples 6 to 10 were the same as those of Examples 1 to 5, including the point that phosphonic acid group-introduced PEDOT was dissolved therein and the point that water was used as a solvent. Moreover, the solid electrolytic capacitors of Examples 6a to 10a had the same configuration as the solid electrolytic capacitor of Example 1, except that the solid electrolyte layer was formed from the polymer solution of Examples 6 to 10, and were produced by the same manufacturing method and under the same conditions.
[0087] The polymer solution of Reference Example 1 and the solid electrolytic capacitor of Reference Example 1a were also prepared. The polymer solution of Reference Example 1 was the same as that of Comparative Example 1, including the addition of ammonia, except that the pH was set to 10. The solid electrolytic capacitor of Reference Example 1a had the same configuration as Comparative Example 1a, except that the polymer solution of Reference Example 1 was used, and was prepared by the same method and under the same conditions as Comparative Example 1a.
[0088] (Characteristics test) The filter liquid permeability of the polymer solutions of Examples 6 to 10 and Reference Example 1 was measured. The electrostatic capacitance (Cap) and equivalent series resistance (ESR) of the solid electrolytic capacitors of Examples 2a to 5a and Reference Example 1a were also measured. The methods and conditions of the filter liquid permeability test and the Cap and ESR measurement tests were the same as those of Example 1, Comparative Example 1, and Example 1a and Comparative Example 1a.
[0089] The measurement results are shown in Table 3 below. (Table 3) TIFF2025032804000005.tif111161
[0090] As shown in Table 3 above, the capacitance of all the solid electrolytic capacitors of Examples 6a to 10a, which have a pH of 10, is further improved. The polymer solutions of Example 10 and Reference Example 1, which contain a primary amine or ammonia, exhibit good liquid permeability in a 0.1 μm pore size filter liquid permeability test due to the pH of 10, and the phosphonic acid group PEDOT is solubilized.
[0091] The polymer solution of Reference Example 1 containing ammonia was also solubilized at a pH of 10, and the capacitance of the solid electrolytic capacitor of Reference Example 1a was also improved. However, it was confirmed that the solid electrolytic capacitors using the polymer solutions of Examples 1a to 4a and Examples 6a to 9a containing secondary amines and tertiary amines had capacitances exceeding that of Reference Example 1a.
[0092] (Examples 11 and 12) The polymer solutions of Examples 11 and 12 and the solid electrolytic capacitors of Examples 11a to 12a were prepared. The polymer solution of Example 11 contains diethylamine, but is different from Examples 3 and 7 in that the pH is adjusted to 8. The polymer solution of Example 12 contains diethylamine, but is different from Examples 3 and 7 in that the pH is adjusted to 11. In addition, the polymer solutions of Examples 11 and 12 are the same as the polymer solutions of Examples 3 and 7, including the point that phosphonic acid group-introduced PEDOT is dissolved and the point that water is used as a solvent. In addition, the solid electrolytic capacitors of Examples 11a to 12a have the same configuration as the solid electrolytic capacitor of Example 1a, except that the solid electrolyte layer is formed with the polymer solutions of Examples 11 and 12, and were prepared by the same manufacturing method and under the same conditions.
[0093] A polymer solution of Reference Example 2 and a solid electrolytic capacitor of Reference Example 2a were also produced. The polymer solution of Reference Example 2 was the same as Reference Example 1, including the addition of ammonia, except that the pH was set to 11. The solid electrolytic capacitor of Reference Example 2a had the same configuration as Reference Example 1a, except that the polymer solution of Reference Example 2 was used, and was produced by the same method and under the same conditions as Reference Example 1a.
[0094] (Characteristics test) The filter liquid permeability was measured for the polymer solutions of Examples 11 and 12 and Reference Example 2. The electrostatic capacitance (Cap) and equivalent series resistance (ESR) were also measured for the solid electrolytic capacitors of Examples 11a and 12a and Reference Example 2. The methods and conditions for the filter liquid permeability test and the Cap and ESR measurement tests were the same as those for Example 1 and Comparative Example 1, and Example 1a and Comparative Example 1a.
[0095] The measurement results are shown in Table 4 below, together with those of Comparative Example 1 and Comparative Example 1a. (Table 4) TIFF2025032804000006.tif81161
[0096] As shown in Table 4 above, the solid electrolytic capacitors of Examples 11a and 12a have a higher capacitance than Comparative Example 1a. Therefore, it was confirmed that the capacitance of the solid electrolytic capacitor can be improved by adding phosphonic acid group-introduced PEDOT and amine to the polymer solution.
[0097] However, based on the results of Example 11a at pH 8, it can be confirmed that Examples 1a to 10a at pH 9 to 10 are more solubilized and have a significantly improved capacitance. Based on the results of Example 12a at pH 11, it can be confirmed that Examples 1a to 10a at pH 9 to 10 are solubilized and dedoping is well suppressed, achieving a high degree of compatibility between high capacitance and low ESR. Therefore, it was confirmed that the pH is preferably 9 or more and 10 or less, and more preferably near pH 9.
[0098] The solid electrolytic capacitor using the polymer solution containing ammonia obtained a good capacitance when the pH was 11. However, since the pH was 11, dedoping proceeded, and the ESR of the solid electrolytic capacitor of Reference Example 2a became high.
[0099] (Particle size distribution measurement) The particle size distribution of the phosphonic acid group-introduced PEDOT was measured in the polymer solution of Example 3 having a pH of 9, the polymer solution of Example 7 having a pH of 10, the polymer solution of Example 11 having a pH of 8, and the polymer solution of Example 12 having a pH of 11. In addition, polymer dispersions of Reference Examples 3 to 5 containing PEDOT:PSS as a conductive polymer and adjusted to various pH values were prepared, and the particle size distribution of PEDOT:PSS was measured.
[0100] Here, PEDOT:PSS is poly(3,4-ethylenedioxythiophene) doped with polystyrene sulfonic acid (PSS). The polymer dispersions of Reference Examples 3 to 5 were prepared as follows. First, PEDOT:PSS was added to water, and dispersed and stirred using ultrasonic waves. In Reference Example 3, pH adjustment was not performed using an alkaline compound. Therefore, the pH of the polymer dispersion of Reference Example 3 was 1.8. In this way, the polymer dispersion of Reference Example 3, in which the concentration of PEDOT:PSS was 2 wt%, was prepared.
[0101] For Reference Example 4, after dispersion and stirring, diethylamine was added to the polymer dispersion until the pH of the polymer dispersion reached 9. This resulted in the preparation of the polymer dispersion of Reference Example 4, in which the concentration of PEDOT:PSS was 2 wt%. For Reference Example 5, after dispersion and stirring, ammonia was added to the polymer dispersion until the pH of the polymer dispersion reached 9. This resulted in the preparation of the polymer dispersion of Reference Example 5, in which the concentration of PEDOT:PSS was 2 wt%. The concentrations of the phosphonic acid group-introduced PEDOT in Examples 3, 7, 11 and 12 were also 2 wt%.
[0102] The particle size distribution was measured by dynamic light scattering. Specifically, a sample with a conductive polymer concentration of 2 wt% was not diluted, and a particle size distribution meter (Nikkiso, Nanotrac UPA-UT151) was used with a measurement range of 0.8 nm to 6.5 μm. The measurement results were then analyzed to determine the D50 value, which is also the median diameter, and the D90 value, which is the particle size corresponding to 90% of the cumulative distribution.
[0103] The calculation results of particle diameters D50 and D90 for Examples 3, 7, 11 and 12 and Reference Examples 3 to 5 are shown in Table 5 below. (Table 5) TIFF2025032804000007.tif126148
[0104] As shown in Table 5 above, in Reference Example 3 where no pH adjustment was performed, the conductive polymer particles of PEDOT:PSS are on the order of micrometers at D50 and D90. Considering Reference Examples 4 and 5 based on Reference Example 3, Reference Examples 4 and 5 are still on the order of micrometers at D50 and D90 even though the pH is adjusted to 9, and are no different from Reference Example 3.
[0105] On the other hand, as shown in Table 5 above, in Example 3 in which phosphonic acid group-introduced PEDOT was used as the conductive polymer and the pH was adjusted using an amine, the conductive polymer particles were reduced in size and solubilized to the 1 nanometer range at D50 and D90 when the pH reached 9. The particle size was approximately 1 / 5000 of that in Reference Examples 3 to 5. In Examples 7 and 12 in which the pH was 10 and 11, respectively, the conductive polymer particles were also in the 1 nanometer range at D50 and D90, similar to Example 3.
[0106] Therefore, as shown in Tables 2, 3 and 4 above, the capacitance of each of Examples 3, 7 and 12 is greatly improved. That is, it was confirmed that by combining phosphonic acid group-introduced PEDOT with an amine and preferably setting the pH to 9 or more, the conductive polymer particles are made smaller and more soluble, and the capacitance is improved. As for Example 11, it can be confirmed that at pH 8, the solubilization and reduction in particle size are still in progress. Therefore, as shown in Table 4 above, the capacitance is starting to become higher than that of Comparative Example 1, but in order to further improve the capacitance, the pH is preferably 9 or more.
Claims
1. a polymer of 3,4-ethylenedioxythiophene having a methylenephosphonic acid group introduced into an ethylenedioxy skeleton; The alkaline compound is amine, excluding ammonia. A conductive polymer solution for capacitors, characterized by:
2. the amine being a secondary amine or a tertiary amine; 2. The conductive polymer solution for a capacitor according to claim 1,
3. The pH is 10 or less; 3. The conductive polymer solution for a capacitor according to claim 2,
4. pH is 9 or more; 4. The conductive polymer solution for a capacitor according to claim 3,
5. The pH is about 9.
4. The conductive polymer solution for a capacitor according to claim 3,
6. an anode foil having a dielectric oxide film formed thereon; A solid electrolyte layer including a conductive polymer; Equipped with The conductive polymer is a polymer of 3,4-ethylenedioxythiophene having a methylenephosphonic acid group introduced into an ethylenedioxy skeleton, the solid electrolyte layer contains an amine except for ammonia as an alkaline compound; A solid electrolytic capacitor characterized by:
7. A method for manufacturing a solid electrolytic capacitor having an anode foil on which a dielectric oxide film is formed, comprising the steps of: a step of forming a solid electrolyte layer by applying the conductive polymer solution for a capacitor according to any one of claims 1 to 5 to an anode foil and drying the applied conductive polymer solution; A method for producing a solid electrolytic capacitor comprising the steps of:
Citation Information
Patent Citations
Capacitor and its method for manufacturing
JP2006287182A
Capacitor and method of manufacturing the same
JP2014067949A
Electrolytic capacitor and method for manufacturing same
WO2018123255A1